2015
DOI: 10.2105/ajph.2014.302420
|View full text |Cite
|
Sign up to set email alerts
|

The Enduring Effects of Smoking in Latin America

Abstract: Objectives. We estimated smoking-attributable mortality, assessed the impact of past smoking on recent mortality, and computed expected future losses in life expectancy caused by past and current smoking behavior in Latin America and the Caribbean. Methods. We used a regression-based procedure to estimate smoking-attributable mortality and information for 6 countries (Argentina, Brazil, Chile, Cuba, Mexico, and Uruguay) for the years 1980 through 2009 contained in the Latin American Mortality Database (LAMBdA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The increase in LE between 2003 and 2016 in Chile was lower than in Brazil [10] and the United States [23]. Mathers et al [24] have shown that mortality rates in old age in middle and high income countries, including Chile, have been consistently decreasing. Others have suggested that increases in LE at 50 years of age in Latin America are slowing, attributable to the impact of smoking [25].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in LE between 2003 and 2016 in Chile was lower than in Brazil [10] and the United States [23]. Mathers et al [24] have shown that mortality rates in old age in middle and high income countries, including Chile, have been consistently decreasing. Others have suggested that increases in LE at 50 years of age in Latin America are slowing, attributable to the impact of smoking [25].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking prevalence is lower in Mexico than in the United States (Palloni et al 2015) and appears to account for part of the adult HHP at older ages in the United States (Blue and Fenelon 2011). However, little is known about smoking-SES gradients among MFB in the United States (see Buttenheim et al 2010; Riosmena and Dennis 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, its use has markedly increased since 1950, and is now considered the second most common cardiovascular risk factor, following high blood pressure 30 . This has led to an increase in cancer deaths and a drop in life expectation of 2–6 years 31 . In Maracaibo, high prevalence of cigarette smoking and MS has been observed, which may suggest an existing relationship between these variables 6, 32 .…”
Section: Discussionmentioning
confidence: 99%